HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN PLASENTA PREVIA DI RSUD RADEN MATTAHER PROVINSI JAMBI - Ayu Mustika Handayani (MIDWIFERY HEALTH JOURNAL, 2019)
According to WHO, maternal deaths caused by bleeding are reported to range from 15-20% due to placenta previa and the incidence is 0.8-1.2% for each birth. The purpose of this study was to determine the relationship of age and maternity parity with the incidence of Placenta Previa at Raden Mattaher General Hospital in Jambi Province in 2018. The results of this study were mostly at risk (67.9%) and those who were not at risk (32.1%). Whereas at risk parity (52.8%) and risk parity (47.2%). Based on the age chi-square test analysis, it has a relationship with the incidence of Placenta Previa with a p value of 0.002 with a value (OR) of 4,365 Trust Intervals (1,780 - 10,706) and there is a relationship of parity with the incidence of Placenta Previa with p-value 0,000 with a value (OR) 7,115 Confidence Interval (3,018-16,774) mothers who have risky parity have a significant chance of 7,115 times to experience Placenta Previa.